2020
DOI: 10.3390/su12177082
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Fungal Community Dynamics and Shaping Factors During Agricultural Waste Composting with Zeolite and Biochar Addition

Abstract: Bacterial and fungal communities play significant roles in waste biodegradation and nutrient reservation during composting. Biochar and zeolite were widely reported to directly or indirectly promote microbial growth. Therefore, the effects of zeolite and biochar on the abundance and structure of bacterial and fungal communities and their shaping factors during the composting of agricultural waste were studied. Four treatments were carried out as follows: Run A as the control without any addition, Run B with ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 57 publications
4
4
0
Order By: Relevance
“…Such observation is supported with our data on genotoxic assay in which the micro slides depicted that there was no quantifiable DNA damage in nano zeolite treated cells as compared to the control cultures. These results corroborates with the recent findings of Wu et al, (2020) who reported zeolite enriched compost showed enhanced microbial growth indicating that these materials have no toxic effects.…”
Section: Resultssupporting
confidence: 93%
“…Such observation is supported with our data on genotoxic assay in which the micro slides depicted that there was no quantifiable DNA damage in nano zeolite treated cells as compared to the control cultures. These results corroborates with the recent findings of Wu et al, (2020) who reported zeolite enriched compost showed enhanced microbial growth indicating that these materials have no toxic effects.…”
Section: Resultssupporting
confidence: 93%
“…The pH of the pile increased, whereas the moisture decreased as the composting progressed (Fig .1 b,c). The results corresponded with a previous study which reported that the biochar addition increased the pH of the composting pile, which was due to the alkalinity properties of the biochar 23 . The physicochemical properties suggest that the enhancement of composting process could be due to the addition of biochar which improves the microbial activities for organic matter degradation.…”
Section: Resultssupporting
confidence: 91%
“…In this study, thermophilic bacteria ceased to grow and then decreased because metabolic products had inhibited bacterial development or organic matter for bacterial nutrition had depleted. It is in line with Wu et al (2020) which stated that the total organic matter and nitrate are the most important factors of bacterial and fungal population change during the composting process. The present study also confirms regarding interactions with indigenous microorganisms, the changes in C/N ratio and temperature affect the survival of pathogenic microbes in the composting process.…”
Section: Total Bacteria On the Mixed Substrate Of Sheep Dung And Rice...supporting
confidence: 87%